A robust enzymatic reporter system for the extremely thermophilic anaerobic bacterium Anaerocellum bescii - Galindo, Joey L.; Tjo, Hansen; Conway, Jonathan M. (Frontiers in Microbiology, 2026)
Thermophilic anaerobic organisms, particularly species that can naturally degrade lignocellulosic biomass, show great promise for next generation bioprocessing. This has led to the development of nascent genetic systems to metabolically engineer these non-model organisms. However, a major challenge remains a lack of reliable reporter systems compatible with the combination of thermophilic and anaerobic growth conditions. Additionally, native glycoside hydrolases in these organisms limit the usefulness of traditional glycosidic enzyme reporters (e.g., LacZ) because of the native background activity present on para-nitrophenyl glycoside substrates. Here we describe the development of a robust enzymatic reporter system that overcomes these challenges in Anaerocellum (f. Caldicellulosiruptor) bescii, an anaerobic, extremely thermophilic (Topt ~ 78 °C), lignocellulolytic bacterium. Our method is based on heterologous expression of hyperthermophilic archaeal galactosidases: an ⍺-galactosidase from Pyroccous furiosus (Pf⍺gal), and a β-galactosidase from Caldivirga maquilingensis (Cmβgal). We show that these reporters produce strong, orthogonal signals on colorimetric substrates at high temperatures (≥90 °C) that eliminate background activity from endogenous galactosidases. We then demonstrate the capability of Cmβgal, the stronger of the two reporters, to distinguish differences in levels of expression between A. bescii promoter sequences, which we verify through qRT-PCR. With its high signal to noise ratio and relative ease of use, this reporter system offers a straightforward and robust method for assessing protein expression in A. bescii and potentially other anaerobic thermophilic organisms, opening doors to improved genetic tools and metabolic engineering applications for industrial biotechnology.